A Comparative Study of Online and Modular Distance Learning of Third-Year BEED College Students at Bestlink College of the Philippines: Vol.3, No.1C (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2024)
In recent months, the demand for online learning has risen significantly. Online Distance Learning is used for any learning across distance, not in a traditional classroom.  Meanwhile, Modular Distance Learning features individualized instruction using Self-Learning Modules in print or digital format.  Bestlink College of the Philippines provided students with two learning modalities for the education continuum and to mitigate the immediate impact of school closure without putting aside the quality of education. In addition, the researchers aimed to determine and compare the two learning modalities which were found to impact students’ performance levels directly and to determine the problems faced by the students who utilized their chosen modality. The study used the comparative descriptive method and sampled thirty (30) students from third-year Bachelor of Elementary Education who have experienced utilizing Online and Modular Distance Learning.  They served as the respondent who provided their responses through the Google Forms survey. In choosing the respondents, the researchers used the purposive sampling method.